284 Treatment strategies and survival of women with sex cord stroma cell tumours – an analysis of the ago-corsett database. (4th December 2020) - Klar, Maximilian; Plett, Helmuth; Heitz, Florian; Kommoss, Stefan; Keul, Jaqueline; Roser, Eva; Czogalla, Bastian; Bossart, Michaela; Link, Theresa; Hasenburg, Annette
Abstract : Introduction/Background: Malignant sex cord stroma cell tumours (SCST) account for less than eight percent of ovarian malignancies. The Arbeitsgemeinschaft fuer Gynaekologische Onkologie (AGO) has established a clinicopathological (Current Ovarian geRm cell and SEx cord stromal Tumour Treatment strategies, CORSETT) database for a better documentation and understanding of this rare disease. Here, we present the first clinicopathological descriptive analysis for patients with independently confirmed SCST from the CORSETT database. Methodology: 20 German centres entered mixed retro- and prospective data of SCST patients with tumour specimens available treated between 2000 to 2014 into the CORSETT database. An independent CORSETT pathology reference panel checked the primary histological diagnosis. We conducted a descriptive analysis of the treatment strategies and created Kaplan-Meier curves and cox regression analyses for the survival analysis. Results: The reference pathology panel diagnosed 143 patients with granulosa cell (GCT, FIGO stage I= 120, 87.0%) and 14 patients with Sertoli-Leydig cell (SLCT, FIGO stage I = 11, 91.7%) tumours (others = 5). The median age of patients with GCT was 57.6 years (SLCT: 47.2 years). 87 of GCT (61.7%) and eight SLCT (57.1%) patients were treated with laparoscopy and the tumour ruptured intraoperatively in 22% (SLCT: 7.7%) of the cases. 57 GCT (45%) and eight SLCT (57%) patients received fertility-sparing surgery. 19 of GCT (15%) and two SLCT (15.4%) patients received adjuvant chemotherapy. 59 of GCT (45%) and two of SLCT (14.3%) patients experienced a disease recurrence. The median progression-free survival (PFS) for all SCST patients was 80.4 months, (overall survival not reached). Advanced FIGO stage was associated with decreased PFS (p < 0.05). Adjuvant chemotherapy had no statistically significant beneficial effect on PFS (all regimens p > 0.05). Conclusion: In this analysis, almost every fourth SCST patient treated surgically experienced an intraoperative cyst rupture that had however no impact on disease recurrence. One in five SCST patient received adjuvant chemotherapy that had no PFS improvement. Disclosures: